MUTU ORGANOLEPTIK DAN KIMIA ABON IKAN GABUS (CHANNA STRIATA) YANG DISUBSTITUSI SUKUN (ARTOCARPUS ALTILIS) - Widia Dara; Arlinda Arlinda (LLDIKTI Wilayah X, 2017)
The aim of research was to determine the effect of substitution breadfruit (Artocarpus altilis) organoleptic quality and chemical content shredded. This research is experimental, with five treatments. Organoleptic tests carried snake head with breadfruit substitution processed into shredded. The study was conducted using a CRD (completely randomized design) with five treatments and two replications. Analyses were performed using analysis of variance to see the effect of adding breadfruit between treatments. If the results differ significantly (F count> F table) then continued with DNMRT test at 5% level. Chemical proximate analysis conducted shredded. Shredded most preferred is the treatment of C made from snake head 83.37% and 16.33% breadfruit. The protein content decreased with increasing number of substitutions breadfruit, otherwise the fiber content increases. Chemical Ingredients shredded were 438 Calories, 31.5% carbohydrate, 19.8% protein, 25.9% fat, 8% ash content and moisture content of 14.8% and 1,12 g fiber. Shredded is made of snake head 83.37% and 16.33% breadfruit meet standard SII shredded. Except for the water content is still rather high (14.8%) is in excess of the permitted standards SII shredded by 10%.